Evaluation of clinical patterns of adult patients presenting with acute poisoning in the emergency at Birat Medical College Teaching Hospital - Gaire, M; Gyawali, S; Karki, S (Devdaha Medical Journal, 2025)
Introduction: Poisoning is one of the major public health concerns worldwide that requires prompt emergency care, owing to its high morbidity and mortality rates. It is also one of the leading causes of visits to the emergency room. This study focused on identifying clinical presentation and outcomes (discharge, mortality, site of treatment, and duration of hospital stay) in adult patients presenting with acute poisoning due to various etiologies at Birat Medical College Teaching Hospital (BMC-TH) in Nepal. Methods: This was a descriptive cross-sectional hospital-based study conducted among patients attending the emergency room of Birat Medical College Teaching Hospital from August 2024 to January 2025. The study was started after ethical approval from the Institutional Review Committee (Reference No: IRC-PA-404/2024). The inclusion criteria consisted of adult patients aged 18 years or above who were diagnosed with acute poisoning based on history, examination, and laboratory parameters. Collected data was performed using structured questionnaires and analysis was performed by using Microsoft Excel. Convenience sampling method was used. Results: A total of 85 cases of acute poisoning were included. The majority of sufferers were younger adults (18–40 years). Males comprised 53%, and females accounted for 47%. Organophosphate (OP) pesticides accounted for the foremost poisoning factor (35.29%), followed by pharmaceutical overdoses (20%) and rodenticides (15.2%). Common symptoms of poisoning had been nausea and vomiting (62%), dizziness (45%), and altered mental status (40%). A common cause for poison intake was suicide (44.2%) and the most common place of intake was home (48.45%). The average period of hospitalization was four days, and in-hospital mortality was 5%, especially due to severe phosphide poisoning (0.85%) and organophosphate poisoning (2.55%). Timely interventions, along with gastric lavage, antidote, and supportive care, were related to better outcomes. Conclusion: Poisoning predominantly affects the young adult population, and among the various etiologies, most common pesticides are organophosphate. This indicates the need to increase awareness amongst the general community, regulate poisonous substances, and construct healthcare resources to lessen the burden of morbidity and mortality because of poisoning in Nepal.